Confocal microscopy reveals in planta dynamic interactions between pathogenic, avirulent and non‐pathogenic Pseudomonas syringae strains. (11th April 2017) - Rufián, José S.; Macho, Alberto P.; Corry, David S.; Mansfield, John W.; Ruiz‐Albert, Javier; Arnold, Dawn L.; Beuzón, Carmen R.
Summary: Recent advances in genomics and single‐cell analysis have demonstrated the extraordinary complexity reached by microbial populations within their hosts. Communities range from complex multispecies groups to homogeneous populations differentiating into lineages through genetic or non‐genetic mechanisms. Diversity within bacterial populations is recognized as a key driver of the evolution of animal pathogens. In plants, however, little is known about how interactions between different pathogenic and non‐pathogenic variants within the host impact on defence responses, or how the presence within a mixture may affect the development or the fate of each variant. Using confocal fluorescence microscopy, we analysed the colonization of the plant apoplast by individual virulence variants of Pseudomonas syringae within mixed populations. We found that non‐pathogenic variants can proliferate and even spread beyond the inoculated area to neighbouring tissues when in close proximity to pathogenic bacteria. The high bacterial concentrations reached at natural entry points promote such interactions during the infection process. We also found that a diversity of interactions take place at a cellular level between virulent and avirulent variants, ranging from dominant negative effects on proliferation of virulent bacteria to in trans suppression of defences triggered by avirulent bacteria. Our results illustrate the spatial dynamics and complexity of the interactions found within mixed infections, and their potential impact on pathogen evolution.